MATHEMATICAL MODELLING AND SIMULATION OF HAZARDOUS PARTICULATE COLLECTION AND SEPARATION IN A MULTICYCLONE COLLECTOR - Djurayev Sherzod Sobirjonovich (Journals Park Publishing, 2025)
This paper develops a detailed mathematical model for capturing and separating solid pollutants inside an industrial multicyclone collector and validates it with Computational Fluid Dynamics (CFD) simulations. The gas flow is described by a simplified form of the Navier–Stokes equations, while particle dynamics include Stokes drag, gravity, centrifugal, and diffusive forces. The model quantifies the collection efficiency η and pressure drop ΔP for particles 1–20 μm in diameter. The average relative error between the model and CFD results does not exceed 4 %, confirming high predictive accuracy. Figure 1 illustrates the agreement between the theoretical curve and CFD data points.
Keywords: Multicyclone collector; particulate pollutants; mathematical modelling; Navier–Stokes; CFD simulation; collection efficiency; pressure drop.